Trisomy of the short arm of chromosome 10. - Nakagome, Y (1975)
A case of a fetus with multiple malformations is described. The mother showed a 46,XX,rcp(10;22) (p11;p11) karyotype. Amniocentesis at the 16th week of gestation revealed that the male fetus had a der(22) chromosome--that is, he was trisomic for a large part of 10p (10pter leads to 10p11). Clinical findings of cases with 10p, 10q, and mosaic 10 trisomies are briefly reviewed.